Diagnostic pathology of nervous system tumours - Ironside, James W.; Moss, Tim H.; Louis, David N.; Lowe, James S.; Weller, Roy O. (Churchill Livingstone, 2002)
Adopting a problem-orientated approach to differential diagnosis, this book covers almost all neoplasms of the central and peripheral nervous systems and their immediate coverings, together with tumours of associated intracranial and spinal structures. It also includes non-neoplastic space-occupying lesions, such as cysts and infective lesions